Two new isoflavones from the roots of Sophora tonkinensis. Issue 2 (1st February 2023) - Chen, Dao-Jun; Yuan, Shuang; Zhang, Peng; An, Qiao; Zou, Ji-Bin; Yuan, Chun-Mao; Zhao, Li-Hua; Hu, Zhan-Xing; Hao, Xiao-Jiang
Abstract: Two new isoflavones (1 and 2 ), as well as eight known ones were isolated from the roots of Sophora tonkinensis Gagnep. Compound 1 represents an unprecedented polymerization pattern constructed by isoflavone and cytisine. Their structures were elucidated by comprehensive spectroscopic data analysis, combined with ECD calculations. Compound 1 displayed significant anti-tobacco mosaic virus (TMV) activity compared with the positive control ningnanmycin. Moreover, compound 6 exhibited potent α -glucosidase inhibitory activity with IC50 value of 47.4 mg/L. Graphical Abstract: UF0001